ENHANCING CNC PRECISION: A REVIEW OF GEOMETRIC ERRORS AND SIMULATION METHODS IN THREE-AXIS CNC SYSTEMS - Tayier, Walisijiang (Journal of Engineering & Technological Advances, 2024)
The rapid expansion in industrial production has markedly increased the deployment of computer numerical control (CNC) systems. Recent efforts have concentrated on optimizing these machines for time-efficient cutting tool operations. The accuracy of CNC systems is heavily dependent on their geometric configurations, but geometric errors such as alignment deviations, backlash, and thermal deformation can compromise structural integrity and operational precision. This review focuses on the role of simulation in three-axis CNC machining, particularly through techniques like finite element analysis (FEA), to predict and mitigate these errors. By examining various CNC machine components, the review highlights how simulation methodologies can address geometric inaccuracies. Key findings indicate that integrating advanced simulation tools with CNC systems effectively reduces geometric errors, enhances machining accuracy, and improves overall system performance. This integration leads to more reliable and precise machining operations, thereby advancing the efficiency and effectiveness of CNC systems in high-precision manufacturing environments.